Beware Neck Pain in a Haemodialysis Patient: Spontaneous Spinal Epidural Haematoma. Issue 1 (January 2017) - Sun, JM; Chen, YH; Chang, CJ; Hsieh, CT
Spontaneous spinal epidural haematoma is a rare and devastating disorder. To the best of our knowledge, only 4 haemodialysis patients with the diagnosis of spontaneous spinal epidural haematoma have been reported in the literature. Here, we reported a 70-year-old male haemodialysis patient who presented with a sudden onset of severe sharp neck pain. Spontaneous spinal epidural haematoma with cord compression from C2 to C6 was diagnosed by magnetic resonance imaging. After emergency surgery, the patient recovered completely from the profound neurological deficits. The relevant literatures were also reviewed.